Holding the line: assembling and mapping local and traditional knowledge of historic injustice and environmental change held by handline fishers in the Cape Agulhas region - Palmer, Brian (Department of Environmental and Geographical Science, 2024)
Small-scale fishers in the Cape Agulhas region of South Africa hold valuable local and traditional knowledge that is insufficiently incorporated in fishery governance. Several meta-level global directives including the Convention for Biodiversity (CBD), United Nations Educational, Scientific and Cultural Organization (UNESCO), and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) call for the incorporation of local knowledge into environmental governance for the sake of achieving more equitable and ecologically sound outcomes. At the national level, the Small-Scale Fisheries Policy (SSFP) calls for stakeholder engagement and the inclusion of local perspectives in management. Additionally, the national Marine Spatial Planning Act (MSPA) addresses the challenges of managing complex social ecological systems by calling for the amalgamation of diverse environmental and human resource usage data through GIS mapping. To date, however, there remains insufficient policy and scholarship dedicated toward outlining methodology for how local and traditional knowledge should be meaningfully and equitably infused into evolving environmental governance toolkits. This research seeks to investigate the ways small-scale fishing knowledge has been historically excluded from fishery governance through lack of consultation and the undervaluing of local perspectives in favor of scientific assessments. By collating historical injustices in the sector this study seeks to identify ways of empowering historically marginalized knowledge holders. Supported by meta-level directives and national policy, this research employs a dual case study in the communities of Struisbaai and Buffeljagsbaai of the Cape Agulhas region. The research is aimed at documenting local and traditional knowledge of small-scale fishers using focus groups, key informant interviews, and mapping surveys. Results of the study demonstrate a wealth of local knowledge held by small-scale fishing communities that remains underutilized in fishery governance. The study results illustrate the need for more widespread ethnographic research and the refinement of methodology so that cultural data can achieve parity with ecological and economic knowledge.